Telestroke for the Treatment of Ischemic Stroke in Western China During the COVID-19 Pandemic: A Multicenter Observational Study - Chen, Ning; Wu, Xintong; Zhou, Muke; Yang, Rongdong; Chen, Daofeng; Liao, Ming; Deng, Yongyi; Hong, Zhen; Zhou, Dong; He, Li (Frontiers in Neurology, 2022)
Background: Intravenous thrombolysis is still underutilized in patients with acute ischemic stroke (IS) in China. A promising strategy for addressing this issue, especially in situations such as the global pandemic of coronavirus disease (COVID-19), is the telestroke mode, which remains to be widely implemented in China. The present study aimed to assess the effects of telemedicine for patients with stroke in Western China, as well as the impact of the pandemic on telestroke services in one year after the COVID-19 outbreak. Methods: In this 2-year multicenter observational study, we retrospectively collected data from 10 hospitals within the Sichuan Telestroke andTelethrombolysis Network. Demographic and clinical characteristics of patients with IS and those relevant to thrombolysis were compared between the pre-telestroke and post-telestroke phases, and between the periods before and after declaration of the COVID-19 pandemic. Results: A total of 11,449 admissions with a primary diagnosis of IS were recorded during the study period. Prior to telestroke implementation, 6.7% of patients (n = 367) received intravenous thrombolysis, and the proportion increased to 7.4% (n = 443; p = 0.084) in the post-telestroke phase. The thrombolysis rate was 7.4% during the COVID-19 pandemic and in the latter half of the year when the viral spread was better controlled in China. The mean door-to-needle time (DNT) was significantly shorter after implementation of the telestroke network (63.76 ± 13.50 vs. 52.66 ± 25.49 minutes; p < 0.001). Conclusions: Telemedicine is effective in improving thrombolysis administration among patients with IS in Western China. Implementation of the telestroke network should be promoted, especially when access to care is affected by public health emergencies such as the COVID-19 pandemic.